karlymk
karlymk
04-06-2020
Mathematics
contestada
Solve for x: -3x-3=-3(x+1)
Respuesta :
yessimarsandoval4
yessimarsandoval4
04-06-2020
Answer:
Has infinite many solutions. X=1
Step by step:
-3x-3=-3(x+1)
-3x-3=-3x-3
-3x-3+3=-3x-3+3
-3x=-3x
Answer Link
soincddw
soincddw
13-11-2020
Answer:
x= -6 broo
Step-by-step explanation:
Answer Link
VER TODAS LAS RESPUESTAS ( 83+ )
Otras preguntas
what are the possible values of x if (4x – 5)2 = 49? check all that apply. -4/5 -1/2 3 5 7
at what value of x does the graph of the following function f(x) have a vertical asymptote f(x)=4x/3x-6
The inequality x > y is satisfied by point (5, 5). true false
Joining two or more independent clauses creates a(n) __________
C=6/(6+12)*180 help please
When may a hypothesis be revised?
Write a polynomial function of minimum degree with real coefficients whose zeros include those listed. Write the polynomial in standard form. 4, -14, and 5 + 8
due to ocean acidification, some localized areas of the ocean _____. are acidic are neutral are increasing their ph are decreasing their ph
Give 5 examples each of application and system software
Two triangles that have the same side length will always be congruent true or false?